The Risk Factors for Weaning Failure of Mechanically Ventilated Patients With COVID-19: A Retrospective Study in National Medical Team Work - Zhao, Hua; Su, Longxiang; Ding, Xin; Chen, Huan; Zhang, Hongmin; Wang, Jinglan; Long, Yun; Zhou, Xiang; Zhang, Shuyang (Frontiers in Medicine, 2021)
Purpose This study aimed to explore the risk factors for weaning of invasive mechanically ventilated patients with COVID-19 pneumonia. Methods Patients diagnosed with COVID-19 pneumonia were selected from the special intensive care unit(ICU) of the Sino-French New City Branch of Tong Ji Hospital，Wuhan, who treated by National Medical Team Work. They were divided into successful weaning (SW) group (N=15) and unsuccessful weaning (USW) group (n=18) according the prognosis. Information of these patients was analyzed. Results There were 33 patients included in this study, we compared the mechanical parameters of the first day of intubation or admittance to the ICU and the worst in the observation days. By comparison, we found that the platform pressure (Pplat), driving pressure (DP) of the USW group after intubation(initial)were higher , compliance was lower than those of the SW group, but there was no difference between positive end-expiratory pressure(PEEP), PCO2, and PO2/FIO2(P/F). Comparing the worst respiratory mechanics parameters of the two groups, the results of the Pplat, DP, compliance and PEEP were same as initial, The PCO2 of the USW group was higher, while the P/F was lower. A Cox logistic regression analysis suggested that higher Pplat was an independent risk factor, higher compliance and lower DP were protective factors for weaning of invasive mechanically ventilated patients with COVID-19 pneumonia. Conclusions Higher Pplat was a risk factor，a higher compliance and a lower DP were protective factor for the weaning of ventilated COVID-19 patients. Mechanical ventilation settings will affect the patient's prognosis.